Bacteria-specific pro-photosensitizer kills multidrug-resistant Staphylococcus aureus and Pseudomonas aeruginosa - Min Lu (Nature Portfolio, 2021)
Multidrug-resistant bacteria are a real threat to human health. Here, the authors investigate a combinatory strategy using blue-laser and thymol against Staphylococcus aureus and Pseudomonas aeruginosa. Blue-laser and thymol succesfully sterilized acute infected or biofilm-associated wounds and prevented systematic dissemination in mice. Compared with mammalian cells, bacteria contain abundant proporphyrin-like compounds that transform harmless thymol into blue-laser sensitizers, thymoquinone and thymohydroquinone. Photo-excitation of thymoquinone and thymohydroquinone augmented reactive oxygen species production in bacteria while completely sparing the host tissue.